1974
DOI: 10.2307/3053023
|View full text |Cite
|
Sign up to set email alerts
|

Why the “Haves” Come Out Ahead: Speculations on the Limits of Legal Change

Abstract: This essay attempts to discern some of the general features of a legal system like the American by drawing on (and rearranging) commonplaces and less than systematic gleanings from the literature. The speculative and tentative nature of the assertions here will be apparent and is acknowledged here wholesale to spare myself and the reader repeated disclaimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
457
0
18

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,108 publications
(538 citation statements)
references
References 22 publications
12
457
0
18
Order By: Relevance
“…This is not surprising. As Gramatikov and Porter (2011:172) observed, "power is the currency of disputes," with dispute resolution often occurring, as Galanter (1974) described, within a framework of myriad power imbalances. Moreover, the broader selfefficacy literature points to confidence being an important influence on behavior across a range of domains, including health behavior (e.g., Strecher et al 1986;Grembowski et al 1993), career development (e.g., Dawes et al 2000), and athletic performance, where "research has demonstrated self-confidence to be one of the most influential cognitive determinants of athletic performance" (Beattie et al 2011:184).…”
Section: A Measuring Legal Confidencementioning
confidence: 99%
“…This is not surprising. As Gramatikov and Porter (2011:172) observed, "power is the currency of disputes," with dispute resolution often occurring, as Galanter (1974) described, within a framework of myriad power imbalances. Moreover, the broader selfefficacy literature points to confidence being an important influence on behavior across a range of domains, including health behavior (e.g., Strecher et al 1986;Grembowski et al 1993), career development (e.g., Dawes et al 2000), and athletic performance, where "research has demonstrated self-confidence to be one of the most influential cognitive determinants of athletic performance" (Beattie et al 2011:184).…”
Section: A Measuring Legal Confidencementioning
confidence: 99%
“…The reliance on science in political conflicts might reproduce existing advantages for the 'haves' because industry and other powerful actors may exert control over debates (Brown et al 2004;Galanter 1974;Kinchy 2010;Sarewitz 2004). It also provided new possibilities for social movements that 'often adopt scientized repertories of contention, such as using counter-experts, publicizing suppressed studies, and carrying out their own participatory research' (Kinchy 2010: 3).…”
Section: Social Movements Science and Expertisementioning
confidence: 99%
“…Approaches and foci within legal mobilization are diverse and researchers in this field understand litigation as part of a complex, multifaceted relationship. Generally, studies of legal mobilization, while focusing on litigation, focus on it as one of multiple avenues of political action, resulting from complex and indeterminate strategic decision-making, and unequally accessible across different levels of society (McCann, 2008, 524-525) For example, studies of legal mobilization may rely heavily on the idea of the dispute pyramid, in which actual litigation is rare in comparison to the amount of claimable grievances (Miller and Sarat 1980), or on the observation that "repeat players" and "one-shotters" have differing levels of legal resources, thus making litigation a far less impactful source of policy change for some (Galanter, 1974). Both of these claims would cast litigation in a limited role in explaining some forms of political mobilization.…”
Section: Explore the Importance Of The Problemmentioning
confidence: 99%